2011
DOI: 10.1093/humrep/der062
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait analysis suggests polymorphisms of estrogen-related genes regulate human sperm concentrations and motility

Abstract: Quantitative trait analysis based on a limited number of genetic markers suggests that estrogen-related genes mainly regulate sperm concentration and motility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 93 publications
1
17
0
1
Order By: Relevance
“…Knowledge of how SHBG is produced in the liver and functions in the blood and within sex steroid target tissues helps us understand the way these genetic polymorphisms might contribute to disease causes. Hip bone mineral density [38] Atherosclerosis [46] rs1799941 Promoter " (A allele) (TAAAA)n [47] Hip bone mineral density [38] Type 2 diabetes [48] Sperm production and motility [49] rs6257 Breast cancer [47,50] Endometrial cancer [42] Sperm production and motility [49] SHBG, sex hormone-binding globulin; SNP, single-nucleotide polymorphism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of how SHBG is produced in the liver and functions in the blood and within sex steroid target tissues helps us understand the way these genetic polymorphisms might contribute to disease causes. Hip bone mineral density [38] Atherosclerosis [46] rs1799941 Promoter " (A allele) (TAAAA)n [47] Hip bone mineral density [38] Type 2 diabetes [48] Sperm production and motility [49] rs6257 Breast cancer [47,50] Endometrial cancer [42] Sperm production and motility [49] SHBG, sex hormone-binding globulin; SNP, single-nucleotide polymorphism.…”
Section: Resultsmentioning
confidence: 99%
“…The most well studied is a variable (TAAAA) n pentanucleotide repeat located within an Alu element upstream of SHBG promoter [43]. Individuals carrying more than 6 TAAAA repeats have lower serum SHBG levels and higher free androgen levels [37,44 & ], and this polymorphism has been associated with the age of menarche and numerous clinical conditions (Table 1) [45][46][47][48][49][50]. Other SNPs exist in SHBG regulatory regions (Table 1) including the common rs1799941 located close to the transcription start site, where the A and G alleles are associated with higher and lower plasma SHBG levels, respectively [38].…”
Section: Genetic Basis Of Inter-individual Differences In Sex Hormonementioning
confidence: 99%
“…Several studies have suggested that hormone levels may be heritable and may predispose individuals to subclinical HH [23,[83][84][85][86][87]. Additionally, polymorphisms in the androgen receptor and trinucleotide repeats may account for a large proportion of the subclinical HH.…”
Section: Discussionmentioning
confidence: 99%
“…Following IGF-I treatment of humans and mice suffering from primary growth hormone resistance, serum IGF-I level increased drastically and led to a substantial increase in serum LH, FSH and testicular testosterone [37], [38]. Moreover, polymorphisms in androgen receptor [39], estrogen receptors [40] and aromatase [39], [40] genes have been shown effective on human sperm concentration and motility. In addition to FSH and LH, IGF-I is thus an essential requirement for sexual development and testicular function (see [41] for a review).…”
Section: Discussionmentioning
confidence: 99%